Analysis of Traditional Child Plays Based on Child Culture and Child Development - Lindberg, Emine Nihal; Cingi, Mehmet Akif; Güzel, Hande (Journal of History Culture and Art Research, 2020)
In this study, traditional child plays were examined in the scope of child culture and their impacts on child development. The first part of the study includes the compilation of traditional children's plays which have different contents and are played in different regions of Turkey. The second part consists of examining the aspects of these plays related to child development. In order to reach traditional children's plays, research articles/books/proceedings and the reviews made by independent researchers and the Ministry of Education in Turkey were examined. A total of 51 plays were selected according to nine different criteria based on the socio-cultural approach. The criteria were geographical region of the play, number of players, gender of players, age of players, timing of the play (day, night, weekday, weekend, etc.), the play space, tools used in the play, the rules of the play and the way to play. Moreover, the impacts of the plays on child development were examined in six different fields of child development: physical, social, moral, emotional, cognitive, and sexual. The main concern in this part was to be able to describe behaviours related to a particular development objectively. In analyses, the first step was to create the first general categories and subcategories from the data. With these categories, an initial analysis form was compiled. Then the form was revised and evaluated by three experts in terms of content validity. By using the revised form, the analysis was made by three coders. Inter-coder reliability was calculated as 0.87. The results showed that plays were played outside the home, in mixed groups, and mostly by using objects such as stones and sticks found in nature. It also seemed that play was considered as a leisure activity which is more suitable for the early age children and used mostly for supporting the development or improvement of physical skills.